Quorum Sensing Modulates the Epibiotic-Parasitic Relationship Between Actinomyces odontolyticus and Its Saccharibacteria epibiont, a Nanosynbacter lyticus Strain, TM7x - Bedree, Joseph K.; Bor, Batbileg; Cen, Lujia; Edlund, Anna; Lux, Renate; McLean, Jeffrey S.; Shi, Wenyuan; He, Xuesong (Frontiers in Microbiology, 2018)
The ultra-small obligate parasitic epibiont, TM7x, the first and only current member of the long-elusive TM7 (Saccharibacteria) phylum to be cultivated, was isolated in co-culture with its bacterial host, Actinomyces odontolyticus subspecies actinosynbacter, XH001. Initial phenotypic characterization of the TM7x-associated XH001 co-culture revealed enhanced biofilm formation in the presence of TM7x compared to XH001 as monoculture. Genomic analysis and previously published transcriptomic profiling of XH001 also revealed the presence of a putative AI-2 quorum sensing (QS) operon, which was highly up-regulated upon association of TM7x with XH001. This analysis revealed that the most highly induced gene in XH001 was an lsrB orthologue, which encodes a putative periplasmic binding protein for the auto inducer (AI)-2 quorum sensing (QS) signaling molecule. Further genomic analyses suggested the lsrB operon in XH001 is a putative hybrid AI-2/ribose transport operon as well as the existence of a luxS orthologue, which encodes the AI-2 synthase. In this study, the potential role of AI-2 QS in the epibiotic-parasitic relationship between XH001 and TM7x in the context of biofilm formation was investigated. A genetic system for XH001 was developed to generate lsrB and luxS gene deletion mutants in XH001. Phenotypic characterization demonstrated that deletion mutations in either lsrB or luxS did not affect XH001’s growth dynamic, mono-species biofilm formation capability, nor its ability to associate with TM7x. TM7x association with XH001 induced lsrB gene expression in a luxS-dependent manner. Intriguingly, unlike wild type XH001, which displayed significantly increased biofilm formation upon establishing the epibiotic-parasitic relationship with TM7x, XH001ΔlsrB, and XH001ΔluxS mutants failed to achieve enhanced biofilm formation when associated with TM7x. In conclusion, we demonstrated a significant role for AI-2 QS in modulating dual-species biofilm formation when XH001 and TM7x establish their epibiotic-parasitic relationship.